Cost optimality and net-zero energy in the renovation of Portuguese residential building stock – Rainha Dona Leonor neighbourhood case study - Ferreira, Marco António Pedrosa Santos (2014)
Cost optimality and nearly-zero energy buildings are two fundamental concepts within the current European Union policy related to the energy performance of buildings and consequently related to climate change mitigation and non-renewable resources consumption. While cost optimality is mainly focused on costs, nearly-zero energy buildings are focused on low energy consumption levels and on-site renewables harvesting. Using a residential building from a social housing neighbourhood, this study investigates the most cost-effective packages of renovation measures to achieve a zero energy balance building and compares these packages with those resulting from the calculation of cost-optimal levels. The investigation on the trade-offs between both approaches is relevant to achieve a smooth transition from cost-optimal levels to nearly-zero energy buildings. The results show that the measures that lead to the cost-optimal levels are very similar to the ones needed to achieve the zero energy balance and the results do not change much when variations on the energy prices, discount rates or photovoltaic costs are considered.